Phosphorylation and activity of the tumor suppressor Merlin and the ERM protein Moesin are coordinately regulated by the Slik kinase. - Hughes, S.C.; Fehon, R.G. (Journal of Cell Biology, 2006)
Merlin and Moesin are closely related members of the 4.1 Ezrin/Radixin/Moesin domain superfamily implicated in regulating proliferation and epithelial integrity, respectively. The activity of both proteins is regulated by head to tail folding that is controlled, in part, by phosphorylation. Few upstream regulators of these phosphorylation events are known. In this study, we demonstrate that in Drosophila melanogaster, Slik, a Ste20 kinase, controls subcellular localization and phosphorylation of Merlin, resulting in the coordinate but opposite regulation of Merlin and Moesin. These results suggest the existence of a novel mechanism for coordinate regulation of cell proliferation and epithelial integrity in developing tissues.